An improved edge ring crack torsion configuration for mode-III fracture characterization. (19th May 2023) - Gong, Yu; Li, Zhaobin; Gao, Yuting; Lin, Wenjuan; Zhang, Jianyu; Zhao, Libin; Hu, Ning
Highlights: An improved edge ring crack torsion configuration for mode III fracture characterization. A better uniformity of mode III SERR distribution along the circular delamination front. The applicability of a semi-analytical formula for the calculation of mode III SERR is investigated. Robustness analysis on the improved edge ring crack torsion configuration is performed. Abstract: Studies on the mode-III delamination are relatively rare compared with those on mode-I, mode-II, and mixed mode-I/II delamination. Currently, there is still no test standard established for mode-III delamination. The most challenge is how to obtain a pure mode-III delamination meanwhile with a good uniform SERR distribution at the delamination front. This work proposes an improved edge ring crack torsion (ERCT) configuration. Numerical results show that the unwanted mode-I and mode-II components are eliminated. In addition, a more uniform distribution of mode-III SERR along the delamination front is obtained, which is conducive to achieving stable delamination growth. The applicability of a semi-analytical formula for the calculation of mode-III SERR is also investigated, which is found to be dependent on the initial pre-crack diameter. In addition, robustness analysis on the modified ERCT configuration is performed, including the effects of the ellipticity of the delamination front, and the horizontal and oblique deviations between the loading head axis and the specimen central axis.